Correlation between Grammatical and Pragmatic Competences among Indonesian University EFL Learners (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
Language competence not only refers to the underlying knowledge of the linguistic aspects of the language system under study, such as grammar and lexis, but also an understanding of the extra-linguistic features of a given communicative scenario, all of which contribute to meaning and the interpretation of meaning, This study aims to: (1) to determine whether there is a correlation between EFL Indonesian university students’ grammatical competence and their pragmatic competence, and (2) to investigate the influence of students’ grammatical competence towards their pragmatic competence. The data collected are from year 2 English students by using grammatical and pragmatic tests for students to answer. Their answers were analyzed quantitatively to obtain the mean score and further will be compared. The results show that: 1) students perform low on both aspects (m1=8.78, and m2=10.46, 2) there is a moderate positive correlation between the two sections (r=.54, p=0.01), and 3) students’ grammatical knowledge contributes on their pragmatic knowledge on medium level (t(65)=-.36, p=0.01). The average level of achievement that students could attain on grammar shows that it is still a challenging aspect in FL learning despite they have received 4 compulsory grammar subjects. This challenge should be taken into concern as the result of this study also shows that grammatical competence could affect learners’ initial competence on pragmatic as week. Therefore, there is a need of improvement on EFL teaching methods especially for grammatical subjects due to very low achievement on this central skill which will contribute to the other skills.
Keywords: Correlation; EFL; Grammatical; Pragmatic